Quantification of the mixed-valence and intervalence charge transfer properties of a cofacial metal–organic framework via single crystal electronic absorption spectroscopy. Issue 20 (9th May 2020) - Doheny, Patrick W.; Clegg, Jack K.; Tuna, Floriana; Collison, David; Kepert, Cameron J.; D'Alessandro, Deanna M.
Abstract : Gaining a fundamental understanding of charge transfer mechanisms in three-dimensional Metal–Organic Frameworks (MOFs) is crucial to the development of electroactive and conductive porous materials. Abstract : Gaining a fundamental understanding of charge transfer mechanisms in three-dimensional Metal–Organic Frameworks (MOFs) is crucial to the development of electroactive and conductive porous materials. These materials have potential in applications in porous conductors, electrocatalysts and energy storage devices; however the structure–property relationships pertaining to charge transfer and its quantification are relatively poorly understood. Here, the cofacial Cd(ii )-based MOF [Cd(BPPTzTz)(tdc)]·2DMF (where BPPTzTz = 2, 5-bis(4-(pyridin-4-yl)phenyl)thiazolo[5, 4- d ]thiazole, tdc 2− = 2, 5-thiophene dicarboxylate) exhibits Intervalence Charge Transfer (IVCT) within its three-dimensional structure by virtue of the close, cofacial stacking of its redox-active BPPTzTz ligands. The mixed-valence and IVCT properties are characterised using a combined electrochemical, spectroelectrochemical and computational approach. Single crystal electronic absorption spectroscopy was employed to obtain the solid-state extinction coefficient, enabling the application of Marcus–Hush theory. The electronic coupling constant, H ab, of 145 cm −1 was consistent with the localised mixed-valence properties of both this framework and analogous systems that use alternative methods to obtain the H ab parameter. This work demonstrates the first report of the successful characterisation of IVCT in a MOF material using single crystal electronic absorption spectroscopy and serves as an attractive alternative to more complex methods due to its simplicity and applicability.